Valores éticos y su aporte en el comportamiento de los estudiantes de educación básica de la unidad educativa “José María Estrada Coello” de la ciudad de Babahoyo, Provincia de “los Ríos”. - Arana Calvache, Alexandra Elizabeth (2015)
This research was performed to determine the ethical values and contributions in the behavior of basic education students of the educational unit José María Estrada coello City Province Babahoyo rivers. Chapter I, it is the problematic contextual field, here the problematic situation where your problem is pointed out to investigate their questions, their work objectives that outline the way to attain and justification where arises highlights the significance, feasibility and beneficiaries. Chapter II, is the theoretical framework that part of the research background, conceptual framework based scientific content in documentary research, it is referred to and quoted for validation, along with their respective hypothesized variables is determined. Chapter III, is the methodology of work, corresponding to the type of employee research, the population to which the sample was extracted, sources of information obtained by applying the data collection instruments, the same as those analyzed and They interpreted to punctuate the respective conclusions and recommendations as an alternative to improving the problemati